Crianças investigam para aprender ciências: uma experiência de aprendizagem na educação pré-escolar - Varela, Paulo; Alves, Elisabete (Góndola, enseñanza y aprendizaje de las ciencias, 2021)
This article describes and analyses the exploration of research activity on the influence of light and humidity on the behaviour of earthworms, promoted in a group of children in preschool education, within the scope of a supervised pedagogical intervention project through the analysis of the process, which focuses on the activity diary, prepared from participant observation. We characterize the spontaneous knowledge of children about earthworms, promoting scientific processes to investigate the influence of light and moisture in conduct earthworms. The analysis suggests that children of these ages assume a "scientific and investigative attitude" constructing knowledge when stimulated appropriately by the teacher, involving interesting and challenging learning experiences.